The Influence of CHSE on Tourists' Interest in Selecting Star-Rated Hotels Post-COVID-19 Pandemic in Gili Trawangan - Christie, Fleury; Lalu Muhammad Furkan (Journal of Entrepreneurship & Business, 2025)
Pupose: The purpose of this study is to investigate how travelers' interest in selecting star-rated hotels is influenced by cleanliness, health, safety, and environmental sustainability (CHSE) in Gili Trawangan after the COVID-19 pandemic. Method: Associative research using a quantitative technique is the research design used. A survey using primary data sources that provide quantitative information on the number of domestic and foreign visitors to Gili Trawangan is the approach used to acquire the data. The study's population consists of all visitors to Gili Trawangan, both domestic and foreign. We use 90 samples for this study. Result: The findings of the data analysis show that the variables related to cleanliness, health, safety, and environmental sustainability all have a positive and significant impact on interest in making a purchase. The variables related to cleanliness, on the other hand, do not significantly affect interest in making a purchase.